Whole Genome Comparative Genomic Hybridization of Ewing Sarcoma Indicates Cytoskeleton, Migration and Protein Trafficking - Burçin Baran (Proceedings, 2018)
Ewing sarcoma is a bone and soft tissue tumor either neuroectodermal or mesenchymal originated and affecting children and adolescents. In the present study, we aimed to find out prognostic and predictive biomarkers for Ewing sarcoma. Hence, we examined the copy number alterations (and related possible genes) among ten Ewing sarcoma patient samples and possible associations with the clinical outcome. DNA extraction from formalin fixed paraffin embedded archive tissues was performed. Whole genome Comparative Genomic Hybridization (CGH) was performed by NimbleGen and recorded as single Panel Rainbow through chromosomes 1–22, X and Y. Data was interpreted by SignalMap software and genetic regions matching the deletion or amplification loci were recorded. The mean age of the patients was 8.6 years. Three of the cases were male, while seven were female. According to CGH analysis, the most common DNA copy number alterations were found in SLIT-ROBO Rho GTPase activating protein (srGAP2), RANBP2 like GRIP domain (RGPD5), nephrocystin 1 (NPHP1), GTF2I repeat domain containing 2 (GTF2IRD2), pyridoxal dependent decarboxylase domain containing 1 (PXDC1), which were found down-regulated among 7 of 10 patients. In conclusion, in our dataset the copy number alterations are mostly found in genes related with cytoskeletal elements, migration and protein trafficking among our patient group. Gene functional studies are required for better understanding the role of these genes in Ewing Sarcoma pathogenesis